Analysis Of The Effect Of The Process Of Issuing Health Personnel Licenses Using The Sipandu Medan Application On Health Worker Satisfaction In Dpmptsp Medan City - Syarifah Nurunnisa; Ermi Girsang; Sri Lestari Ramadhani Nasution (International Journal of Health and Pharmaceutical (IJHP), 2023)
In the era of global reform and information, public services by government officials today still have many weaknesses so that they have not been able to meet the quality expected by the community. This is indicated by the existence of various public complaints submitted through the mass media and social networks as well as the results of a community satisfaction survey which stated that the permit issuance process took a long time, the information conveyed was not clear and not transparent. The purpose of this study was to analyze the effect of the process of issuing health worker permits using the Medan Sipandu Application on Community Satisfaction in Dpmptsp Medan City This type of research is Quantitative Analytical research, namely the method in the form of numeric data using a cross sectional approach, with a sample of 200 people. The results of this study are that the variable that has the most influence on the satisfaction of health workers regarding the use of the Sipandu Medan Application is complaint handling. statistical test resultsearned valuep significance is 0.000 <0.05. So it can be concluded that there is an effect of handling complaints on the satisfaction of health workers regarding the use of the Sipandu Medan Application.SIPANDU is here to make it easier for the public to submit related complaints.